Some considerations related to quantum electronics, acoustics and science of material based on experiment and theory - Zoran Latinović; Stanko Ostojić; Branka Kaluđerović; Zoran Fidanovski; Sanja Jevtić; Đurđe Milanović (Zaštita Materijala)
The coupling of some fundamental sciences and issues arising from it are considered in this paper. The transport and optical characteristics belong to nowadays problems of material science. Some measurements and their interpretations for chosen condensed materials are considered. Various processes, which include directly optical and acoustic processes, are measured for solid and liquid materials. After obtained principal issues of measurement, coupling with them is performed. Principal links include dielectric, resistive, optical and acoustical performances. Nonlinear optical contribution up to optical-laser breakdown can be evaluated from linear data. Micellar laser scattering cover transient effects and is one of the topics in many sciences (including biology and ecology).